Spark in motion - Kolter, Jason (Manning, 2019)
"Spark in Motion teaches you how to use Spark for batch and streaming data analytics. In nearly 3 hours of hands-on video lessons, you'll get up and running with Spark, starting with the basic architecture of a Spark application. You'll explore data partitioning and accessing common application state, and then you'll deep-dive into using Spark SQL and dataframes for structured analytics. Finally, you'll use Spark Streaming to handle and process real-time data flowing into your application. When you're doing analytics on big data systems, it can be a challenge to efficiently query, stream, filter, and consolidate data sharded across a cluster. Built especially for efficiently operating over large distributed datasets, the Spark data processing engine takes some of the weight off your shoulders. Spark features an easy-to-use interface, near-limitless upgrade potential, and performance that will knock your socks off. Spark simplifies your data infrastructure so you can focus on creating top-notch analytics."--Resource description page